An Intelligent Career: Taking Ownership of Your Work and Your Life - Arthur, M.; Khapova, S.; Richardson, Julia (2017)
Ultimately, the goal of this book is to help knowledge workers from architects to lawyers learn to work on their own terms and to assume ownership of work and career.